Analisis nilai karakter pada tembang dolanan anak dalam pembelajaran Bahasa Jawa di kelas V Sekolah dasar - Musfaizah, Nur Laela; Chumdari, Chumdari; Karsono, Karsono (Didaktika Dwija Indria, 2021)
The purpose of this study was to identify and describe the development of character values in grade V Pasar Kliwon 1 Surakarta Elementary School through traditional play songs in Javanese language learning. This study used a descriptive qualitative research method with a content analysis approach. The type of content analysis required in this research is sourced from in-depth interviews and archive or document analysis. Data collection techniques used in this study were interviews and documentation studies. The data obtained from this research through in-depth interviews and documentation studies show that there are three children’s play songs along with the character values contained, namely the Lir-Ilir play song with values of a religious character, responsibility, hard work, and independence. Traditional play song of Gundul-gundul pacul with values of a religious character, responsibility, and independence.  While the traditional play song of Padhang bulan with values of a religious character, curiosity, discipline, and responsibility. Overall, the analysis of the character values in children’s songs that are often applied is the value of religious character and responsibility.